Peran Kepolisian Daerah Sumatera Utara dalam Memberantas Pornografi di Era Digital: Perspektif Psikologi Kriminal - Rambe, Sapani Martua; Risdalina, Risdalina; Kumalasari, Indra (CV. Social Politic Genius (SIGn), 2024)
This research aims to examine the role of the North Sumatra Regional Police in combating cyber-pornography offenses in the digital era from a criminal psychology perspective. Field research and normative juridical methods were employed to collect primary and secondary data. Primary data were obtained through in-depth interviews, while secondary data were gathered through a literature review. The data were analyzed using a descriptive qualitative approach. The results indicate that cyber-pornography offenses in North Sumatra are a complex phenomenon with diverse modus operandi. The North Sumatra Regional Police has implemented comprehensive strategies, including strengthening investigator capacity, utilizing digital forensic technology, educating the public, and collaborating with internet service providers. However, challenges remain, such as substantiating digital evidence, navigating cross-border jurisdiction, and keeping pace with rapid technological advancements. In conclusion, synergy among stakeholders and public participation are crucial. Continuous evaluation and refinement of strategies are necessary to address the ever-evolving dynamics of cybercrime, considering the factors that influence criminal behavior in the digital realm.